Common and Distinct Features of Adult Neurogenesis and Regeneration in the Telencephalon of Zebrafish and Mammals - Diotel, Nicolas; Lübke, Luisa; Strähle, Uwe; Rastegar, Sepand (Frontiers in Neuroscience, 2020)
In contrast to mammals, the adult zebrafish brain shows neurogenic activity in a multitude of niches present in almost all brain subdivisions. Irrespectively, constitutive neurogenesis in the adult zebrafish and mouse telencephalon share many similarities at the cellular and molecular level. However, upon injury during tissue repair, the situation is entirely different. In zebrafish, inflammation caused by traumatic brain injury or by induced neurodegeneration initiates specific and distinct neurogenic programs that, in combination with signaling pathways implicated in constitutive neurogenesis, quickly and efficiently overcome the loss of neurons. In the mouse brain, injury-induced inflammation promotes gliosis leading to glial scar formation and inhibition of regeneration. A better understanding of the regenerative mechanisms occurring in the zebrafish brain could help to develop new therapies to combat the debilitating consequences of brain injury, stroke and neurodegeneration. The aim of this review is to compare the properties of neural progenitors and the signaling pathways, which control adult neurogenesis and regeneration in the zebrafish and mammalian telencephalon.